2012
DOI: 10.1039/c2sc20083j
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of plasticizer and plastic explosive detection and differentiation with serum albumin cross-reactive arrays

Abstract: Plastic explosives, such as Semtex and C4, are commonly used explosive mixtures. The differentiation and detection of the plasticizers within these mixtures could provide information for anti-terrorism and combat activities. In this study, we demonstrate a strategy of using cross-reactive serum albumin proteins to differentiate and detect the plasticizers found within these explosive mixtures. With our sensing ensemble, comprised of serum albumins, fluorescent indicators and an additive, we successfully classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…Alternatively, differential responses to ROS might be exploited to obtain “fingerprints” for the different species. Such a strategy is reminiscent of the pattern‐based recognition of peptides,27a,b terpenes,27c flavonoids27d, and plastic explosives27e based on UV/Vis absorption changes. Alkylated coumarins 3 a – d were prepared from 7‐hydroxycoumarin 1 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, differential responses to ROS might be exploited to obtain “fingerprints” for the different species. Such a strategy is reminiscent of the pattern‐based recognition of peptides,27a,b terpenes,27c flavonoids27d, and plastic explosives27e based on UV/Vis absorption changes. Alkylated coumarins 3 a – d were prepared from 7‐hydroxycoumarin 1 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The primary sequence of SAs differs between species, which thus exhibit differences in ligand binding (41). Previously, we have used arrays of SAs for the differentiation of other hydrophobic analytes including fatty acids (48), terpenes (49), and plasticizers (50). However, none of these previous studies involved differences between the analyte structures as subtle as glycerides do, nor had we challenged our methods to identify structural aspects of an unknown.…”
Section: Significancementioning
confidence: 99%
“…It was reported that the explosive power of 2,4,6‐trinitrophenol (TNP) is similar to a highly explosive compound TNT . Apart from its explosive nature, TNP is considered as a main toxic pollutant, which harshly affects soil and ground water and poses a significant health hazard because of its high solubility in water . Short‐term exposure to TNP causes eye and skin irritation, whereas long‐term exposure may cause damage to the kidneys and respiratory organs .…”
Section: Introductionmentioning
confidence: 99%